2009
DOI: 10.1002/app.29867
|View full text |Cite
|
Sign up to set email alerts
|

The study on poly(ether sulfone) modified cyanate ester resin and epoxy resin cocuring blends

Abstract: Poly(ether sulfone) terminated with phenolic hydroxyl groups modified cyanate ester resin and epoxy resin cocuring blends were investigated by differential scanning calorimetry, Fourier transform infrared spectroscopy, scanning electron microscopy, rheometry, and mechanical properties measurement. The results suggested that poly (ether sulfone) (PES) could accelerate the polycyclotrimerization reaction of cyanate ester and cocuring processes between cyanate ester and epoxy of modified blends because of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…On the contrary, low viscosity would cause coalescence and rupture of bubbles during the blowing process. Figure 2 shows the steady shear viscosity of CE60 mixture resin system as a function of time, cured at temperature from 140 C to 180 C. It can be observed that the viscosity of the systems shows a similar tendency and possess an induction period 29,30 (where the increase in viscosity is modest and gradual, followed by an extremely rapid exponential increase in viscosity). The induction period in steady shear viscosity is about 53, 35, 22, and 17 min at 140, 150, 170, and 180 C, respectively, as seen in Figure 2.…”
Section: Resultsmentioning
confidence: 98%
“…On the contrary, low viscosity would cause coalescence and rupture of bubbles during the blowing process. Figure 2 shows the steady shear viscosity of CE60 mixture resin system as a function of time, cured at temperature from 140 C to 180 C. It can be observed that the viscosity of the systems shows a similar tendency and possess an induction period 29,30 (where the increase in viscosity is modest and gradual, followed by an extremely rapid exponential increase in viscosity). The induction period in steady shear viscosity is about 53, 35, 22, and 17 min at 140, 150, 170, and 180 C, respectively, as seen in Figure 2.…”
Section: Resultsmentioning
confidence: 98%
“…However, for their use as matrix resins for structural composites an increase in toughness would still be required. High-T g amorphous thermoplastics (TPs) have been shown to toughen cyanate esters [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Commercial types of polysulphone or polyetherimide can be used, but due to the high molecular weight of all commercial TPs, this is at the expense of a large increase in viscosity of the cyanate-TP blend.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cyanate ester/epoxy resins, a kind of the composite resins, have been widely used in the high frequency substrates [7][8][9]. Epoxy resin contributed the prominent toughness and adhesion to copper [10,11]; cyanate ester contributed the low dielectric constant, low dielectric loss, excellent thermostability [12][13][14][15][16][17] and low water absorption [18,19]. Besides, it was suggested that it need to increase the composition of epoxy resin in the cyanate ester/epoxy composite resin for better toughness [20].…”
Section: Introductionmentioning
confidence: 99%